The Dowry as a Crime in Disguise of Gifts: Evidences from Sadar and Faridganj Upazilla of Chandpur District (Bangladesh Journal of Public Administration, 2019)
Dowry is a despicable affliction in society. The social evil has become a barrier for women in everysphere of life. The culture of dowry can be found not only in sub-continent but also in Europe, China,The United States, and also in African countries. A Dowry means the transfer of property by the brideor her family to the groom as an arrangement of marriage. When a bride or her family pays money orany other movable or immovable property, it is called dowry, which is also known as the bride pricein the sub-continent. Though the dowry is most common in the rural area, it cannot be said that it isabsent in cities. Instead, it is used as a disguise of gifts in women's marriage where the parents of themarriageable woman are bound to give dowry as a gift to the groom. This anathematization of dowryis increasing day by day in society. Social problems like child marriage, physical and mental abuse tothe women, divorce and even killing of women are the consequences of dowry. The government ofBangladesh has taken significant steps to eradicate this practice. The punishment for dowry-relatedcrimes is severe, which has been amalgamated in the Dowry Prohibition Act, 1980. The mostimportant step is to create consciousness among people, especially in the rural areas, to stop thepractice of dowry from the society. This study will help the practice and people of the society to goforward to abate the dowry practice.